Implementasi Kebijakan Corporate Social Responsibility Pada PT. Trimegah Bangun Persada Di Desa Kawasi Kecamatan Obi Kabupaten Halmahera Selatan - Saroa, Elias; Mandey, Lucia; Mandey, Silvia (JURNAL ILMIAH SOCIETY, 2016)
PT. Trimegah Bangun Persada is located in the village Kawasi District of Obi South Halmahera Regency is a nickel mining company is also in addition to seeking profits are also trying to implement corporate social responsibiliti so that in addition to increasing the sompany’s image better in view Stakehoulders also increase the company’s role in improving the welfare and social responsibility enviromental the people around and the people in North Maluku,as it has been in good mandated in Law No.4 of 2009 on mining minerals,article 1 paragraph 3 of Law No.40 of 2007 a limited liability company. The purpose of this study was to analyze the policy implementation of Corporate Social Responsibility PT. Trimegah Bangun Persada in the Village Kawasi Obi District of South Halmahera Regency. The research found that the application of CSR implementation is based on the Memorandum of Agreement between the management of PT. Trimegah Bangun Persada South Halmahera District Government and Rural Society Kawasi which resulted in a 9-point agreement has been implemented as a CSR program. Models or patterns of CSR adopted by the company in the form of direct involvement. The motive for companies to implement CSR is a profit motive, the community, and the environment. CSR implementation benefits include: improving public welfare, environmental protection, community development, rural development as well as the nation. Keywords: Implementation, Policy, Village